The archaeology of the Holy Land from the destruction of Solomon's Temple to the Muslim conquest - Magness, Jodi 1956- (Cambridge University Press, 2012)
This book provides an introduction to the archaeology and history of ancient Palestine – modern Israel, Jordan and the Palestinian territories – from the destruction of Solomon's temple in 586 BCE to the Muslim conquest in 640 CE. Special attention is paid to the archaeology of Jerusalem and the Second Temple period, in the time of Herod the Great and Jesus. For each period, the book offers a historical background for the Mediterranean world and the ancient Near East, as well as the events in Palestine. Major sites such as Masada, Caesarea Maritima and Petra are examined in archaeological and historical detail, along with the material culture – coins, pottery, glass and stone vessels – of each period. This book provides a thorough overview of the archaeology of this historically vibrant part of the world